Guru Pendidikan Agama Islam Menjadi Solusi Dalam Meningkatkan Kesidiplinan Siswa - zaini, bahruddin (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2024)
Student discipline is a critical aspects of the educational process in schools. Good discipline fosters an effective and conducive learning environment that enchances both academic and non-academic achievements and shapes a positive characters in students. Islamic Religious Education teachers play a significant role in in addressing diciplinary  among students through an approachment rooted in Islamic values. This research aims to explore the efforts and roles of Islamic Religious Education teachers in improving student discipline in schools. Islamic Religious Education takes a personal approach to students who show less disciplined behavior, providing advice, guidance and improve their attitudes and behavior. Additionally, parental involvement and collaboration with school authorities are essential strategies that used by Islamic Religious Education teachers to effectivekly address disciplinary issues